Psychiatric morbidity in psoriasis: a study in Himachal Pradesh, India - Kashyap, Subhash; Kumar, Ajay; Kumar, Ramesh; Shanker, Vinay (International Journal of Research in Medical Sciences, 2017)
Background:Psychiatric morbidity in psoriasis is influenced by socio-cultural factors. Most of the studies in this perspective are done in western setup; to extrapolate them on Indian patients with different demographic and socio-cultural profile may not be appropriate. Our study was designed to evaluate the prevalence and its correlation to various socio-economic variables in Indian patients. Methods: This was a non-interventional, cross-sectional study, in which 125 consecutive psoriasis patients over one year were screened for psychiatric morbidity. Demographic and disease parameters including Psoriasis Area and Severity Index (PASI), Psoriasis Disability Index (PDI), General Health Questionnaire (GHQ), Comprehensive Psychopathological Rating Scale (CPRS) were recorded along with the severity assessment of psychiatric morbidity and its relation to these variables was analyzed. Results: Among 125 psoriasis patients, 43 (35.2%) had psychiatric morbidity. Thirty two (26.4%) had depression, 3 (2.4%) had dysthymia, generalized anxiety disorder and adjustment disorder each, and 2 (1.6%) suffered social phobia. A significant increase in psychiatric morbidity was seen with increase in PDI and PASI scores. Conclusions: There is a significant psychiatric morbidity associated with psoriasis and it increases with severity of the disease.